2016
DOI: 10.1111/gwmr.12157
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Groundwater Flow in Monitoring Wells by Altering Dissolved Oxygen

Abstract: In this study, the dissolved oxygen (DO) alteration method (Chlebica and Robbins 2013) is used to evaluate the patterns of flow into and vertically within shallow screened monitoring wells. The method entails bubbling air into a well, followed by conducting DO profiles with time. Tests were conducted in six standard 2" (5 cm) polyvinyl chloride shallow screened monitoring wells at four test sites in Storrs, Connecticut. Test sites vary in formation permeability, flow patterns, and nearby geographic features in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…The static well head of SIMA 2 had an elevation of 179.88 m, which resulted in a head difference of 4.46 m from SIMA 1. These wells are known to be hydraulically connected based on observed drawdown in pumping tests (Cagle ) and studies using the dissolved oxygen alteration method (Vitale and Robbins ). The latter showed that the fracture at the depth of 16.5 m in SIMA 1 was connected to the 13.1 m fracture in SIMA 2.…”
Section: Resultsmentioning
confidence: 99%
“…The static well head of SIMA 2 had an elevation of 179.88 m, which resulted in a head difference of 4.46 m from SIMA 1. These wells are known to be hydraulically connected based on observed drawdown in pumping tests (Cagle ) and studies using the dissolved oxygen alteration method (Vitale and Robbins ). The latter showed that the fracture at the depth of 16.5 m in SIMA 1 was connected to the 13.1 m fracture in SIMA 2.…”
Section: Resultsmentioning
confidence: 99%
“…The presence of the probe is assumed to have a negligible effect on DO concentrations. Based on testing in Chlebica and Robbins (2013) and Vitale and Robbins (2016), DO profile repeatability in stagnant zones indicates that mixing from density gradients does not have a measureable impact on vertical movement in the well over the course of hours to days, and is therefore assumed to be negligible relative to advective flow in the well in this study. The procedure was tested in Sima 1 using two Instrumentation Northwest (INW) manufactured DO probes.…”
Section: Methodsmentioning
confidence: 99%
“…Vertical movement of the diluted zones showed vertical in‐well flow direction. Chlebica and Robbins () and Vitale and Robbins () determined that flow was the primary factor in changing DO concentration and that the effects of biotic or abiotic reactions were negligible, in the time frame of testing. Gas tracers have two distinct advantages over liquid tracers.…”
Section: Introductionmentioning
confidence: 99%
“…Such occurrences can be important for contaminated site cleanup and research has focused on understanding concentration data collected from monitoring wells (Reilly et al 1989;Church and Granato 1996;Elci et al 2001;Ma et al 2011;McMillan et al 2014;Vitale and Robbins 2016). However, the differences in construction between water supply wells and monitoring wells, primarily casing diameter and length of well screen, create the potential for greater flows through supply wells where there is less resistance to flow as well as greater head difference between shallow and deep strata.…”
Section: Transport Impacts From Intraborehole Flowsmentioning
confidence: 99%